The effect of competition from open source software on the quality of proprietary software in the presence of network externalities - Mingqing Xing (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: A growing number of open source software emerges in many segments of the software market. In addition, software products usually exhibit network externalities. The purpose of this paper is to study the impact of open source software on the quality strategies of proprietary software vendors when the market presents positive network externalities. Design/methodology/approach: To analyze how open source software affects the quality of proprietary software, this paper constructs two vertical differentiation models: the basic model considers proprietary software monopolizing the market, and the extended model considers proprietary software competing with open source substitute. Findings: This paper mainly finds that the presence of open source software does not necessarily lead to the improvement of proprietary software quality. The network externalities and the compatibility between open source and proprietary software can change the impact of open source software on the quality of proprietary software and affect the quality strategies of proprietary software vendors under certain conditions. Originality/value: The main contribution of this paper is to examine the effect of open source software on the quality strategies for proprietary software vendors in software markets with network externalities.
Keywords: 650; quality strategy; open source software; proprietary software; functional quality; software usability; network externality; compatibility